Promoting Third Graders’ Executive Functions and Literacy: A Pilot Study Examining the Benefits of Mindfulness vs. Relaxation Training - Cordeiro, Carolina; Magalhães, Sofia; Rocha, Renata; Mesquita, Ana; Olive, Thierry; Castro, São Luís; Limpo, Teresa (Frontiers in Psychology, 2021)
Research suggested that developing mindfulness skills in children improves proximal outcomes, such as attention and executive functions, as well as distal outcomes, such as academic achievement. Despite empirical evidence supporting this claim, research on the benefits of mindfulness training in child populations is scarce, with some mixed findings in the field. Here, we aimed to fill in this gap, by examining the effects of a mindfulness training on third graders’ proximal and distal outcomes, namely, attention and executive functions (viz., inhibitory control, working memory, and cognitive flexibility) as well as literacy-related achievement (viz., handwriting fluency, text quality, Portuguese grades). These outcomes were measured with behavioral tasks and teacher ratings. Sixty-six Portuguese children were randomly allocated to an experimental group receiving mindfulness training (n = 29) or an active control group receiving relaxation training (n = 37). Both training programs were implemented by psychologists in two 30-min weekly sessions for eight weeks. All students were assessed before and after the interventions. Three main findings are noteworthy: (a) mindfulness training enhanced teacher-rated cognitive flexibility and a performance-based composite score of executive functions among children with higher pretest scores; (b) relaxation training improved performance-based cognitive flexibility and the composite score of executive functions among children with lower pretest scores; (c) children receiving mindfulness training had higher handwriting fluency and better grades in Portuguese than those receiving relaxation training. These findings provide preliminary evidence on the benefits of mindfulness training in educational settings and highlight the moderating role of baseline performance on those benefits.